PENERAPAN PENDEKATAN CONTEKSTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 001 KASIKAN KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Khasanah, Niswatul; Rivai, Muhammad (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to improve students' science learning outcomes through the application of the Contextual Teaching And Learning (CTL) approach for fifth-grade students at SDN 001 Kasikan, Tapung Hulu District, Kampar Regency, Riau, for the 2023/2024 academic year. This research was conducted from March to April 2024. With a total of 25 students, 15 male students, and 10 female students. The design of this research is Classroom Action Research. (PTK). The parameters measured are student learning outcomes, student activities, and teacher activities. The research instruments used are the question item sheet and the observation sheet for student and teacher activities. The results of the first meeting of Cycle I observations show that the teacher's activity was good at 71.43%, and the second meeting was 78.57% in the good category. For Cycle II, the observation of the teacher's activity increased to the very good category at 92.86% and Cycle II at 96.42% in the very good category. Meanwhile, the students' activities were in accordance with the plan, with the students' activities also increasing to the good category in Cycle 1, meeting 1 at 71.43%, meeting 2 at 85.71%, Cycle II, meeting 1 at 89.29%, and meeting 2 at 92.86% in the very good category. Meanwhile, the students' learning outcomes also showed improvement, with the initial average score of 59.20 increasing to 72.64 in the first cycle and further rising to 81.12 in the second cycle. The percentage of completeness in the first cycle was 68% and in the second cycle was 92%. Thus, it can be concluded that the implementation of the Contextual Teaching And Learning (CTL) model can enhance the science learning outcomes of fifth-grade students at SDN 001 Kasikan, Tapung Hulu District, Kampar Regency.